Effects of the English for Specific Purposes (ESP) on Health Promotion Competence - Sulastri Br Ginting; Tedty R. Tinambunan (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
This study employed a quasi-experimental design with a pre-test and a post-test control group. A total of fifty public health students (n = 25 in the experimental group and n = 25 in the control group) participated in the study. The experimental group (n = 25) received ESP-based training, while the control group (n = 25) received training in General English. The measures of data collection included an English proficiency test, a job readiness test, and a health promotion knowledge test. At a significance level of p = 0.05, statistical analyses using paired samples t-tests and independent t-tests were conducted. The results showed a significant improvement in scores of the experimental group in English proficiency (M = 61.8 to 81.2; p < 0.001), work preparedness (M = 55.9 to 79.4; p < 0.001), and health promotion knowledge (M = 59.3 to 82.7; p < 0.001). No significant improvement was detected in the control group (p > 0.05). The findings indicate that the ESP approach was superior to the traditional General English approach in ensuring the improvement in the linguistic proficiency and vocational readiness of students. The ESP method significantly improved the level of English proficiency, employment readiness, and health promotion knowledge among the students in the field of public health. Incorporating ESP into public health courses can enhance graduates' employability and professional proficiency, equipping them to address challenges in global health communication and promotion.